Enhancing Study Program Accreditation Scores at Islamic University: Developing the Puladasa Data Service Center in Alignment With BAN-PT Version 9 Criteria - Lukman Asha; Sarwo Edy; Sri Rahmaningsih; Eka Apriani; Erfin Wijayanti; Farida Esmianti; Megi Ari Pratama (STAI Hubbulwathan Duri, 2024)
This research focuses on the development of the Integrated Data Service Center (PULADASA), a data center used in the accreditation process for study programs. It aims to increase accreditation value in areas like Vision, Mission, Goals, Strategy, Governance, Student Affairs, Human Resources, Finance, Facilities, Education, Research, Community Service, and Achievement. Expert assessment by 2 media experts, namely Material Experts, and assessment by 17 study programs as users. This Integrated Data Service Center (PULADASA) service, as well as knowing user responses to the Integrated Data Service Center (PULADASA) that has been developed. This research is research and development (RD). Data analysis in this study used quantitative and qualitative analysis. Quality variables are arranged based on display aspects, programming aspects, media completeness aspects, language, implementation, and ease of operation. Student response variables to learning media are arranged based on a grid, namely: navigation structure, appearance, and language. Based on the assessment by 2 experts on the One-Stop Data Service Center (PULADASA), it received a score of 87.6 from the ideal maximum score of 120, so it is included in the good category (B) with an ideal percentage of 80%. The assessment by 17 study programs showed students scored 102.5 out of 120, indicating a very good category (SB) with an ideal percentage of 85.5%. The one-stop data service center (PULADASA) can assist in accreditation processes with nine standards, with a user response score of 859.